Abbreviated breast biopsy procedure by registration of craniocaudal and mediolateral breast MR images - Haarburger, Christoph; Ruther, Johannes; Truhn, Daniel; Schrading, Simone; Bug, Daniel; Kuhl, Christiane K.; Merhof, Dorit (Proceedings - International Symposium on Biomedical Imaging, 2018)
Dynamic contrast enhanced magnetic resonance imaging (MRI) of the breast requires injecting a contrast agent to detect suspicious lesions with high sensitivity and specificity. To reduce motion artifacts and shorten scan time, craniocaudal compression of the breast is performed during diagnostic imaging. If a lesion is found to be suspicious, MRI-guided breast biopsy might be necessary. So far, this requires a mediolateral compression of the breast and a second application of contrast agent for localization of the lesion. The proposed algorithm registers images of a breast under both types of compressions such that the location of lesions marked in a craniocaudal image can be transformed into the corresponding mediolateral image. Thus, localization during the biopsy procedure can be performed without application of contrast agent. Performance is evaluated for 31 lesions and yields a median localization accuracy of 3.6 mm.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Breast biopsy; Breast mri; Breast registration; Deformable registration; MR-guided biopsy